Spatial and temporal variability of dry spells in Akola district - ANNA, SHIVAKUMAR; SATPUTE, G. U.; APTURKAR, S. M. (Journal of Soil and Water Conservation, 2021)
The spatial and temporal variability of rainfall and its uneven and inadequate distribution determines the failure of crops especially in drought prone areas. Knowledge of the distribution of dry spells during the monsoon period is essential for successful planning of rainfed farming. In the present study daily rainfall data for the period 1998-2015 were analyzed for different talukas of Akola district for the study of dry spells. The spatial and temporal variation of dry spells at all the talukas of Akola district was analyzed using starting dates of dry spells of different severity/duration and spatial variation maps for this parameter were developed. The spatial variation of highest period dry spells among different taluka places under each dry spell duration classes viz. 2 to 3 weeks, 3 to 4 weeks, 4 to 5 weeks and more than 5 weeks was observed 18, 25, 33 & 45 days at Balapur and 19, 25, 30 & 45 days at Murtizapur talukas followed by 18, 24, 33 & 42 days at Akola and 18, 25, 29 & 41 days at Patur talukas respectively. It is useful for mitigating the losses due to occurrence of dry spells and also suggest the contingency measures (sowing windows, mulching, spraying of anti transparent, supplemental irrigation and rainwater harvesting and its recharging) against dry spells when the crop is under moisture stress.